163 TRANSHITAL ESOPHAGECTOMY IN THE TREATMENT OF ESOPHAGEAL SQUAMOUS CELL CARCINOMA. (14th September 2020) - Kruel, C; Vieira, F; Schramm, R; Chedid, M; Rosa, A; Vieira, A
Abstract: : In the state of Rio Grande do Sul, Brazil, it is encountered a very high incidence of. esophageal squamous cell carcinoma in the world.(1). Advances in surgical procedure techniques and. postoperative treatment have arisen in esophagectomy, which remains as with significant morbidity. and mortality. Compared to other esophagectomies. conducted with thoracotomy, such as Ivor-Lewis and McKeown techniques, the Transhiatal. esophagectomy has a shorter surgical time, a lower rate of mediastinitis and then lower morbidity. Methods: Ninety-six patients undergoing transhiatal esophagectomy in the Hospital de Clínicas de Porto Alegre, between 2005 and 2017 were evaluated. Thirteen patients underwent neoadjuvant treatment with chemoradiotherapy. Ninety-day survival and 5-year survival were evaluated. Results: Overall 90-day survival was 91.7%. The overall 5-year survival was 41.2%. Patients undergoing neoadjuvant therapy had a 90-day survival of 100% and a 5-year survival of 74.1%. Patients undergoing frontline esophagectomy had a 90-day survival of 90.3% and 5-year survival rate of 36%. Non-neoadjuvant patients with negative lymph nodes had a 5-year survival of 50.2%. The average surgical time was 253 minutes. Thirty-seven patients (38.5%) had positive lymph nodes in the surgical specimen. Multivariate analysis showed that surgical time and presence of positive lymph nodes are associated with a worse outcome. Conclusion: Patients submitted to transhiatal esophagectomy present considerable long-term survival, which can be amplified in the absence of lymph node involvement. Operated patients who have undergone neoadjuvant therapy prior to surgery demonstrate increased survival times compared with those without treatment. References: 1) Corley DA, Buffler PA. Oesophageal and gastric cardia adenocarcinomas: analysis of regional variation using the Cancer Incidence in Five Continents database. Int J Epidemiol. 2001 Dec;30(6):1415–25.